1968 barra 1973: Um toque do passado - Montagnari, Eduardo F. [UNESP] (Universidade Estadual Paulista (Unesp), 1984)
Esboço para um estudo dos problemas da juventude e da cultura na relação entre Estado e Sociedade durante a conjuntura brasileira de 1968 a 1973.

An outline to the study of the problems concerning youth and culture in the relation State versus society in the Brasilian social context from 1968 throught 1973.
1968/1973: a touch of the past
Keywords: Estado e sociedade; indústria cultural; contracultura; juventude; comportamento social